Pemanfaatan Teknik Painting With Light Pada Objek Foto Perkampungan Nelayan Pantai Drini Gunungkidul Yogyakarta - Nofria Doni Fitri (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2022)
Digital photography to this day has been utilized for human needs. Houses and business stalls with various shapes and styles are evidence of human civilization in the fishing village of Drini Beach, Gunungkidul. This place is crowded with tourists day and night. During the day, it is difficult to get good photos in this place because the situation is disorganized and it looks crowded. This ultimately underlies this experimental-based research carried out at night. Taking pictures at night is a difficult thing to do due to the lack of available lighting. We will try to overcome this lack of lighting with a long exposure technique. Experiment-based research using an artificial LED flashlight as a fill light is used to create this fishing village. This technique is known as